1982
DOI: 10.1152/ajprenal.1982.243.3.f271
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate transport by proximal tubule of the rabbit kidney

Abstract: Oxalate transport was examined in isolated perfused segments of the proximal tubule of the rabbit. When oxalate was present in a concentration of 10(-5) M in the bathing and perfusing solutions, there was a net secretory flux of oxalate of 36.4 +/- 1.4, 34.7 +/- 4.3, and 20.7 +/- 2.8 x 10(-15) mol . min-1 . mm-1 in the superficial S1, S2, and S3 segments, respectively, at a bath temperature of 37 degrees C. The net secretory flux of oxalate in the juxtamedullary S1 and S2 segments was 12.8 +/- 2.5 and 12.5 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…However, these and other studies suggested that more than one secretory system, with different affi nities for oxalate, may be responsible for oxalate handling in mammalian kidneys (129, 137, and 138). The studies of oxalate transport in rabbit kidneys indicated proximal tubules as the main locus of net oxalate secretion, with the S1/S2 and S3 segments having a dominant and minor role, respectively (139). Subsequent experiments linked the Na + -independent transport of SO 4 2-and HCO 3 -in the proximal tubule cell BLM (140, 141) to oxalate, according to which one oxalate is exchanged for one SO 4 2-or two HCO 3 - (142).…”
Section: Figure 3 Transporters Along the Rodent Gastrointestinal Tracmentioning
confidence: 99%
“…However, these and other studies suggested that more than one secretory system, with different affi nities for oxalate, may be responsible for oxalate handling in mammalian kidneys (129, 137, and 138). The studies of oxalate transport in rabbit kidneys indicated proximal tubules as the main locus of net oxalate secretion, with the S1/S2 and S3 segments having a dominant and minor role, respectively (139). Subsequent experiments linked the Na + -independent transport of SO 4 2-and HCO 3 -in the proximal tubule cell BLM (140, 141) to oxalate, according to which one oxalate is exchanged for one SO 4 2-or two HCO 3 - (142).…”
Section: Figure 3 Transporters Along the Rodent Gastrointestinal Tracmentioning
confidence: 99%
“…Perfused segments of the proximal tubule in rabbit demonstrate net oxalate secretion [35]. Anion exchange proteins in the proximal tubule mediate transcellular oxalate excretion and recycling at the brush-border membrane.…”
Section: Renal Handling Of Calcium Phosphate and Oxalatementioning
confidence: 99%
“…The latter transporter functions in multiple exchange modes using oxalate, chloride, formate, sulfate, or bicarbonate as substrates [2,16]. The distal tubule has a minor role in oxalate secretion in rats [19,46] and rabbits [44].…”
Section: Introductionmentioning
confidence: 99%